Kebebasan Beragama dalam Literatur Tafsir bi Al-Ma'tsur : Studi terhadap Tafsir Jami’ al-Bayan fi Tafsir al-Quran, Tafsir al-Quran al-Adzim dan al-Durru Al-Mantsur fi Tafsir bi al-Ma’tsur - Rozi, Fathur (Mahad Aly Al Fithrah, 2024)
Beliefs (religion) are closely related to an individual's spiritual experience and cannot be imposed by anyone. The issue becomes different when the position of religion shifts from being private to entering the public sphere, making the choice of religion no longer an absolute fundamental right but subject to control, often leading to